Journey to Fluency: A Step-by-Step Guide to English Language Proficiency - Diyora, Umarkulova (International Journal on Integrated Education, 2023)
This article provides a step-by-step guide to achieving English language proficiency. It emphasizes the importance of defining goals, regular practice, training with a teacher, immersion in an English-speaking environment, using technology, reading and listening to a variety of materials, practicing conversational skills, testing and evaluating progress, focusing on grammar and vocabulary, recording and self-monitoring progress, finding inspiration, and assessing and correcting mistakes. The article highlights the benefits of mastering English and offers practical tips for learners at all levels.